Angioid streaks. A case report - Aimé Broche Hernández; Mayra Rodríguez Casales; Iusimí Guillén Brizuela (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Angioid streaks are breaks in Bruch's membrane displayed at the bottom of the eye as orange or gray bands around the optic disc, and from that point on they extend radially. There are a number of diseases associated with the development of angioid streaks such as the pseudoxanthoma elasticum, Paget's disease, senile elastosis and hyperplastic fibrous dysplasia or Ehlers-Danlos syndrome. A case of a patient with pseudoxanthoma elasticum who suffers from sudden loss of bilateral visual acuity after a facial trauma is presented.